English language in Saudi Arabia: vision 2030 in the historical prism of a clash between cultures - Almesaar, Oun (Frontiers in Communication, 2024)
This article examines how the English language was and is today perceived within Saudi Arabia, with the help of a historical analysis and qualitative content analysis of the Human Capability Development Program (HCDP) of the Saudi Vision 2030. Based on historical analysis of Saudi-British relations, and works of Tzvetan Todorov and Jacques Lacan, it is concluded that the English language, as a part of the Western culture, is potentially experienced in Saudi Arabia in the intersection of the mirroring dimensions of Idealisation-Demonisation and Mimicry-Disgust. The content analysis of the HCDP yielded the following conclusions: Islam has a place in the Saudi future as long as it's moderate and non-extreme; the preservation of Saudi culture will rely heavily on the preservation of Arabic language, and it will be a carrier of national identity. The Program is for the most part silent with respect to the English language. It is hypothesised that this conflict is removed from the official discourse, but still might be present in the Saudi culture. Future studies should examine this issue by conducting interviews and analysing relevant social media content.